Multi-element constraints on the sources of volatiles to Earth. (15th September 2022) - Sharp, Z.D.; Olson, P.L.
Abstract: A number of studies have used one or several isotopic systems to estimate the origin of Earth's volatiles. Several volatile sources and subsequent volatile loss are generally considered in these models. In this communication, we use a forward model based on the presumed formation history of Earth to simultaneously constrain the sources for seven volatile elements (H, He, N, Ne, Ar, Kr and Xe). We consider the three potential volatile sources: nebular ingassing, chondrites, and comets. Sinks include loss by early hydrodynamic escape and long-term loss of ionized Xe. 10, 000 Monte Carlo simulations generate several hundred solutions that match the abundance of all these elements to within a factor of ∼2 of the present-day Earth values, as well as critical isotope ratios (δ 15 N, 20 Ne/ 22 Ne, 36 Ar/ 38 Ar, Kr and Xe). The source of volatiles is distinctly different for different elements. Our results indicate that there was a large excess of H, He and Ne supplied by nebular ingassing, with subsequent massive loss (>99% He and Ne) by early hydrodynamic escape. Kr and Xe were supplied primarily by comets, and N was supplied almost entirely (>98%) by chondrites. The source of Ar is mixed, with 50–90% chondrites and the remainder from ingassing. Solutions with nitrogen isotope ratios that match Earth values require a > 92% E chondrite source. δ 15 N values are far too high using a C chondrite source (>20‰ vs AIR). Our results suggest late addition of 7.5 ± 0.7 × 10 21 g comets, 8.3 ± 5.6 × 10 24 g C chondrites and 1.2 ± 0.5 × 10 26 g E chondrites. The Kr isotope pattern should follow that of cometary input, given that > 90% of all Kr comes from a comet source. Our results fit the measured values of Comet 67P/C-G within error. Xe isotope data can be matched to Earth values using solar isotope values as an assumed cometary source if we assume a large mass-dependent enrichment factor during loss of ionized Xe to space. The measured isotope data for Comet 67P/C-G have both light and heavy Xe isotope ratios that do not match the Earth atmosphere data, suggesting that this comet is not, in our model, representative of the Earth cometary Xe source. The amount of ingassed H is critically dependent on oxygen fugacity, ranging from 11 to 22 times the present day ocean amount for presumed low f (O2 ) of the early magma ocean. Even at low f (O2 ) values, most of the water is dissolved as H2 O rather than H. A large hydrogen isotope fractionation during hydrodynamic escape (α = 1.6 to 1.7) is required to explain the present-day D/H values. This α value corresponds to equilibrium between H2 and H2 O at ∼300 °C or loss of atomic H to space. Loss of hydrogen early in Earth's history easily accounts the relatively high f (O2 ) of Earth's present-day mantle.